Ophthalmological changes in children with advanced stage of chronic kidney disease: a hospital-based study - Abdullah Al Mamun; Afroza Begum; Mohammad Azmain Iktidar; Faisal Chowdhury; Amit Kumar Datta; Ranjit Ranjan Roy; Tahmina Jesmin; Mohammad Afzal Mahfuzullah (BMJ Publishing Group, 2024)
Background Ocular disorders can arise in the advanced stages of chronic kidney disease (CKD) for various reasons, including uraemia, biochemical abnormalities, hypertension and inadequate haemodialysis treatment.Methods We conducted a cross-sectional study at the Pediatric Nephrology Department, both inpatient and outpatient, of from January 2020 to July 2021. The study aimed to identify and compare ophthalmological changes among children at different stages of CKD to assess potential visual threats. A total of 92 children with advanced-stage CKD, aged 5-18 years, meeting the inclusion and exclusion criteria, were included in the study. Comprehensive assessments, including medical history, physical examinations, relevant tests and detailed ophthalmological examinations, were conducted.Results The mean age of the participants was 12.1±3.68 years. Most of the children were boys (66%). Twenty-nine patients exhibited impaired visual acuity, children with (6/60-6/24) scores in Snellen's chart Lid oedema and conjunctival pallor were observed in 20.7% and 60.9% of cases, respectively, which were found to statistically significant with advancing CKD stages (p<0.001). Dry eyes were found in 9.8% of CKD stage V patients receiving dialysis (VD) (p=0.003). One patient had a posterior subcapsular cataract, and 7.6% had conjunctival congestion. Patients with conjunctival congestion and hypertensive retinopathy had significantly higher levels of serum phosphate and calcium phosphate product (p<0.001). Hypertensive retinopathy was present in 16.3% of cases, with a significantly higher proportion in the haemodialysis group (93%). Haemodialysis patients exhibited higher blood pressure, lower haemoglobin levels, and a more severe reduction in estimated glomerular filtration rate (p<0.001).Conclusion This study highlights the significant ocular complications associated with CKD, underscoring the need for regular ophthalmological screenings.